Endocrine responses to marathon running. Issue 3 (September 1985) - Semple, C G; Thomson, J A; Beastall, G H
Abstract : We have examined the hormone status of ten healthy adult males who completed the Glasgow marathon. Serum thyroxine, free thyroxine, triiodothyronine and thyroid stimulating hormone were unaffected by the exertion. Serum cortisol as well as other steroid hormones, androstenedione, dehydroepiandrosterone sulphate and oestradiol showed distinct rises (p less than 0.01) but serum testosterone fell significantly (p less than 0.01). There was no change in sex hormone binding globulin capacity but a significant fall in LH levels (p less than 0.05) accompanied the fall in serum testosterone. The mechanism of the fall in serum testosterone in this situation requires clarification but it is unlikely to have adverse consequences.